Bibliometric Analysis of Influencing Factors on Nurse Performance - I Dewa Ayu Yulia Adelina; Zairin Noor; Meitria Syahadatina Noor; Erida Wydiamala; Lenie Marlinae (Universitas Malahayati Lampung, 2024)
ABSTRACT Nurse performance is a key factor in determining the success of patient recovery and patient satisfaction with the services provided. This article provides a bibiometric analysis of nurse performance by analysing publication trends, geographical contributions, journal types and research topic networks. Data were collected using the Publish or Perish (PoP) application and visualised using VOSViewer. The results showed that the publication trend related to nurse performance has increased with research topics including nursing, workload, hospital, stress and performance quality. The United States, Iran, China, Australia and Brazil were identified as the main contributors to these publications. This analysis provides a visual overview of research topics related to nurse performance, as well as identifying potential areas for further research. Keywords: Nurse, Workload, Hospital, Stress, Quality, Work Environment, Nurse Performance